Gastroenterology Curriculum in the Canadian Medical School System - ThucNhi Tran Dang; Clarence Wong; Lana Bistritz (Canadian Journal of Gastroenterology and Hepatology)
Background and Purpose. Gastroenterology is a diverse subspecialty that covers a wide array of topics. The preclinical gastroenterology curriculum is often the only formal training that medical students receive prior to becoming residents. There is no Canadian consensus on learning objectives or instructional methods and a general lack of awareness of curriculum at other institutions. This results in variable background knowledge for residents and lack of guidance for course development. Objectives. (1) Elucidate gastroenterology topics being taught at the preclinical level. (2) Determine instructional methods employed to teach gastroenterology content. Results. A curriculum map of gastroenterology topics was constructed from 10 of the medical schools that responded. Topics often not taught included pediatric GI diseases, surgery and trauma, food allergies/intolerances, and obesity. Gastroenterology was taught primarily by gastroenterologists and surgeons. Didactic and small group teaching was the most employed teaching method. Conclusion. This study is the first step in examining the Canadian gastroenterology curriculum at a preclinical level. The data can be used to inform curriculum development so that topics generally lacking are better incorporated in the curriculum. The study can also be used as a guide for further curriculum design and alignment across the country.